2020
DOI: 10.3390/cells9112368
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Exonic Sequencing of Hemiplegic Migraine-Related Genes in a Cohort of Suspected Probands Identifies Known and Potential Pathogenic Variants

Abstract: Hemiplegic migraine (HM) is a rare migraine disorder with aura subtype including temporary weakness and visual, sensory, and/or speech symptoms. To date, three main genes—CACNA1A, ATP1A2, and SCN1A—have been found to cause HM. These encode ion channels or transporters, important for regulating neuronal ion balance and synaptic transmission, leading to HM being described as a channelopathy. However, <20% of HM cases referred for genetic testing have mutations in these genes and other genes with roles in ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Moreover, in a large population of HM patients with no mutation on the main genes (CACNA1A, ATP1A2, or SCN1A), 1.3% of cases presented with a mutation on SLC2A1 and having HM episodes as the main clinical feature (8). Conversely, other studies postulated that SLC2A1 mutations alone might not be sufficient for the development of isolated migraine symptoms and they were not described in patients with HM as a unique clinical manifestation (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in a large population of HM patients with no mutation on the main genes (CACNA1A, ATP1A2, or SCN1A), 1.3% of cases presented with a mutation on SLC2A1 and having HM episodes as the main clinical feature (8). Conversely, other studies postulated that SLC2A1 mutations alone might not be sufficient for the development of isolated migraine symptoms and they were not described in patients with HM as a unique clinical manifestation (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the International Classification of Headache Disorders-3, two different HM subtypes are included: familial and sporadic hemiplegic migraine (6). Mutations in the ion transportation genes CACNA1A, ATP1A2, and SCN1A are well-known to cause HM; despite this, mutations in these genes are found in <20% of HM cases (4,8). Other genes with roles in synaptic function and neurotransmission have also been implicated in the pathogenesis of HM and HM-like disorders such as PRRT2 mutations (4,8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach used to study the complex genetic pathways of this neurological disorder is to examine monogenic subtypes of migraine, 12,27 and there have been a number of multigenerational studies performed on MA pedigrees 29 and unrelated hemiplegic migraine probands. 30,31 Familial Migraine with Aura A study of particular families which show strong inheritance of MA showed that a frameshift mutation of the KCNK18/TRESK gene segregated with migraine diagnosis, suggesting that it was causal. 29 This was further corroborated in a study by Pettingill et al, which demonstrated through the use of CRISPR-Cas9 that frameshift mutations of TRESK are associated with migraine phenotypes.…”
Section: Monogenic Forms Of Migrainementioning
confidence: 99%
“…15,62,63 Several research groups have reported increased diagnostic rates for several neurological diseases, through the use of whole exome sequencing (WES) [64][65][66] and targeted gene panels. [67][68][69] WES analysis has shown that not all suspected HM cases have exonic mutations in the known FHM genes, 30,31 or genes that cause overlapping disorders, which suggests that additional genes or other factors as yet unknown are causative of HM, 12 some of which may be revealed through WES or whole genome sequencing and structural analysis.…”
Section: Hemiplegic Migrainementioning
confidence: 99%